REVIEW OF SOFT SKILLS AMONG TRAINERS FROM ADVANCED TECHNOLOGY TRAINING CENTER (ADTEC) - Amiruddin, Mohd Hasril; Ngadiman, Norhayati; Abdul Kadir, Romy; Saidy, Sukartini (Journal of Technical Education and Training, 2016)
The Advanced Technology Training Centre (ADTEC) institutions under the Ministry of Human Resource are major players for skilled human resource development in Malaysia. In preparing for the competent workforce, ADTECs are taking active measures to ensure that their trainees are equipped with the necessary soft skills –in addition to technical skill - that are much needed to deal with the complex and challenging workplace. However, integrating soft skills into the training that has traditionally emphasised the technical and vocational skills is not an easy task. The diversity of soft skills elements to be developed, the unique nature of the different training programmes and the difficulty in assessing softs skills are some of the challenges that training centres have to contend with. The purpose of this study was to assess the level of soft skills (communication skills, critical problem solving skills, teamwork skills and leadership skills) acquired by trainees and to identify if there is skills acquired are influenced by types of training programmes. A survey design method was used to study two hundred trainees from the final year of four Diploma programmes in the Batu Pahat Advanced Technology Training Centre (ADTEC) who were selected as respondents for the study. Specifically developed soft skills questionnaire was used to gather data on soft skills. Data obtained on soft skills data were subsequently analysed using descriptive and inferential statistical methods. The results of analysis show that trainees do have high level of soft skills and programmes do not seem to have differential influence on acquisition of soft skills.